Anisotropic bonded magnet and preparation method thereof
By spraying the outer surface of the heterosqualitative bonded magnet to form a lubricating layer, the problem of insufficient mechanical strength of the magnet is solved, and better mold release effect and magnetic performance improvement are achieved.
Patent Information
- Application Number
- CN202510236594.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-29
AI Technical Summary
The mechanical strength of existing heterosqualitative bonding magnets is insufficient, which leads to easy damage or deformation during the demolding process, affecting its magnetic and mechanical properties.
A lubricating layer is provided on the outer surface of the magnetic body, and a lubricating layer is formed by spraying a lubricating agent solution to reduce friction between the magnet and the mold, and prevent lubricating agent from mixing into the magnet and interfering with its internal structure.
It effectively realizes that the surface is not damaged or deformed during the release process of the magnet, while avoiding the negative impact of lubricant on the internal structure of the magnet, enhancing the structural strength and magnetic properties of the magnet.
Smart Images

Figure CN119905307A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bonded magnet materials, and in particular to an anisotropic bonded magnet and a preparation method thereof. Background Art
[0002] Bonded magnets have good processing properties and are widely used in motors, power tools, new energy vehicles and other fields. Among them, compared with isotropic magnets, anisotropic bonded magnets have attracted widespread attention due to their superior magnetic properties. At present, the main production method of anisotropic bonded magnets is compression molding, which includes the following steps: mixing a mixture containing magnetic powder and a binder to obtain composite magnetic powder; orienting the composite magnetic powder in a magnetic field, molding, and curing the composite magnetic powder in turn, and finally obtaining anisotropic bonded magnets. During the above compression molding process, the composite magnetic powder and the mold are squeezed against each other, and there is a lot of friction. In order to ensure that the magnet is completely removed from the mold, lubricants are mostly introduced into the composite magnetic powder at this stage to reduce the friction between the composite magnetic powder and the mold. However, the introduction of lubricants will affect the mechanical strength of the magnet, resulting in a decrease in the mechanical strength of the magnet. Summary of the invention
[0003] The main purpose of the present invention is to provide an anisotropic bonded magnet and a preparation method thereof, so as to solve the problem of insufficient mechanical strength of the anisotropic bonded magnet in the prior art.
[0004] In order to achieve the above object, according to one aspect of the present invention, there is provided an anisotropic bonded magnet, which includes a magnetic body and a lubricating layer; the lubricating layer is located on the outer surface of the magnetic body, and the magnetic body includes a magnetic material and a bonding material.
[0005] Further, the thickness of the magnetic body is 1 to 4 mm; and / or,
[0006] The thickness of the lubricating layer is 10 to 30 μm.
[0007] Furthermore, the lubricating layer contains a lubricant; preferably, the lubricant includes at least one of polytetrafluoroethylene, boron nitride, molybdenum disulfide, and stearate.
[0008] Further, the magnetic material includes at least one of NdFeB magnetic powder, SmFeN magnetic powder and SmCo magnetic powder; and / or,
[0009] The bonding material includes an epoxy resin adhesive;
[0010] Further, the mass ratio of the magnetic material to the bonding material is 100:(1.5-3.5); and / or,
[0011] The mass ratio of the magnetic material to the lubricant in the lubricating layer is 100:(0.1-1.0).
[0012] A second aspect of the present invention provides a method for preparing anisotropic bonded magnets, comprising the following steps:
[0013] S1, mixing magnetic material and bonding material to obtain mixed rubber magnetic powder;
[0014] S2, performing a first pressing on the mixed rubber magnetic powder to obtain a first compact;
[0015] S3, spraying a lubricant solution on the outer surface of the first green compact, and obtaining an intermediate after drying;
[0016] S4, placing the intermediate in a magnetic field for a second pressing to obtain a second green compact;
[0017] S5, solidifying the second green compact to obtain anisotropic bonded magnet.
[0018] Further, the lubricant solution is a mixture of a lubricant and an organic solvent, wherein the lubricant includes at least one of polytetrafluoroethylene, boron nitride, stearate, and molybdenum disulfide, and the organic solvent is n-hexane; and / or,
[0019] The magnetic material includes at least one of NdFeB magnetic powder, SmFeN magnetic powder and SmCo magnetic powder; and / or,
[0020] The bonding material includes an epoxy resin adhesive;
[0021] The mass ratio of magnetic material to bonding material is 100:(1.5-3.5); and / or,
[0022] The mass ratio of magnetic material to lubricant is 100:(0.1-1.0); and / or,
[0023] The density of the first compact is 3-5 g / cm 3 .
[0024] Furthermore, the spraying is air spraying, the nozzle diameter used for spraying is 1-3 mm, the gas pressure is 0.2-0.6 MPa, the spraying height is 10-30 cm, the spray gun angle is 45°, the flow rate is 0.5-10.0 L / min, and the spraying speed is 10-50 cm / s.
[0025] Furthermore, the drying temperature is 40 to 60° C., and the drying time is 1 to 3 hours.
[0026] Further, the temperature of the first pressing is 10-30° C.; and / or, and / or, the temperature of the second pressing is 100-200° C., and the intensity of the magnetic field is 1.5-2T.
[0027] Furthermore, the curing temperature is 150-200° C., and the curing time is 60-90 min.
[0028] By applying the technical solution of the present invention, a lubricating layer is provided on the outer surface of the magnetic body. Since the lubricating layer only exists on the outer surface of the magnetic body but is not mixed into the interior of the magnetic body, not only can demolding be effectively achieved, but the interaction between the magnetic material and the bonding material inside the magnet will not be disturbed by additional non-magnetic particles, thereby avoiding the negative impact of the lubricant on the internal structure of the magnet, ensuring that the bonding material can more fully and evenly coat the magnetic material, enhancing the structural strength of the magnet, and thus significantly improving the magnetic properties and mechanical properties of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the cross-sectional structure of anisotropic bonded magnet in one embodiment of the present invention.
[0030] Description of reference numerals:
[0031] 101- magnetic body; 102- lubricating layer. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0033] As described in the background of the present invention, the anisotropic bonded magnet in the prior art has the problem of insufficient mechanical strength. In order to solve the above problem, in a typical embodiment of the present invention, Figure 1 As shown, an anisotropic bonded magnet is provided, which includes a magnetic body 101 and a lubricating layer 102; the lubricating layer 102 is located on the outer surface of the magnetic body 101, and the magnetic body 101 includes a magnetic material and a bonding material.
[0034] The magnetic properties of the anisotropic bonded magnet of the present invention show anisotropy, that is, the magnetic strength of the magnet is different in different directions. In the specific implementation of the present invention, an external magnetic field is applied during the molding process of the anisotropic bonded magnet to obtain anisotropic magnetic properties.
[0035] The magnetic body 101 is the core part of the anisotropic bonded magnet, and is mainly composed of magnetic material and bonding material. The magnetic material is a substance that provides magnetic properties, while the bonding material is used to bond the magnetic materials together to form a magnetic body with a specific geometric shape and mechanical strength. The structure and performance of the magnetic body 101 directly determine the overall magnetic and mechanical properties of the anisotropic bonded magnet.
[0036] The lubricating layer 102 is disposed on the outer surface of the magnetic body 101. It can be understood that at least part of the outer surface of the magnetic body 101 is provided with a lubricating layer, and the outer surface of the magnetic body includes the front and rear end faces and the side surfaces of the magnetic body 101. The main function of the lubricating layer 102 is to reduce the friction between the magnet and the mold during the magnet molding and demolding process, so that the magnet can be smoothly removed from the mold without damaging its surface or causing deformation. By limiting the lubricating layer 102 to the surface of the magnet instead of mixing it into the interior of the magnet, the negative impact of the lubricant on the internal structure and mechanical properties of the magnet can be avoided.
[0037] In the prior art, most of the methods are to mix the lubricant with the magnetic powder and then press it inside the magnet, which not only increases the difficulty of demoulding, but also the residual lubricant particles will become non-magnetic impurities inside the magnet, which will interfere with the effective connection between the magnetic powders, thereby reducing the mechanical properties of the magnet, such as the radial crushing strength. Compared with the prior art, the presence of the lubricating layer 102 of the present invention reduces the friction between the magnet and the mold, so that the magnet can be more easily removed from the mold after molding, avoiding damage or deformation of the magnet surface caused by demoulding difficulties, and helping to maintain the integrity and dimensional accuracy of the magnet; secondly, the present invention can avoid the residual lubricant particles interfering with the effective connection between the magnetic powders by setting the lubricating layer 102 on the outer surface of the magnetic body 101 instead of mixing it into the magnet, ensuring that the binder can more fully and evenly coat the magnetic powder, and enhancing the structural strength of the magnet; in addition, since the lubricating layer 102 only exists on the surface of the magnet, the interaction between the magnetic material and the binder inside the magnet will not be interfered by additional non-magnetic particles, which helps to improve the magnetic properties of the magnet.
[0038] In some embodiments, the lubricating layer 102 is disposed around the entire outer surface of the magnetic body 101, including the front and rear end surfaces and the side surfaces of the magnetic body 101, so that the lubricating layer continuously and evenly covers the surrounding surfaces of the magnetic body, forming a continuous, uniformly thick outer shell layer. Furthermore, on the outer surface of the magnetic body, the coverage rate of the lubricating layer reaches 100%, that is, the entire surface of the magnetic body, ensuring effective isolation between the magnet and the mold.
[0039] In some embodiments, the thickness of the magnetic body 101 is 1-4 mm, for example, 1 mm, 2 mm, 3 mm, 4 mm, or a range consisting of any two thereof.
[0040] In some embodiments, the thickness of the lubricating layer 102 is 10 to 30 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm or any two thereof. By limiting the thickness of the lubricating layer 102 to 10 to 30 μm, the friction during demoulding can be reduced, while avoiding adverse effects on the internal structure of the magnet. This can not only ensure that the magnetic properties of the anisotropic bonded magnet are not affected, but also ensure the effectiveness of the lubricating layer 102. Since the lubricant is only used for surface treatment and not mixed into the magnet as a whole, it will not affect the distribution and orientation of the magnetic material inside the magnet, thereby maintaining the high density and good orientation of the magnetic material inside the magnet. Secondly, the amount of lubricant used can be reduced, the production cost can be reduced, and the loss of magnetic properties caused by excessive lubricant can be avoided; in addition, the lubricating layer 102 on the surface can be used as a protective layer to reduce the direct contact between the magnet and the environment, especially in high temperature, humid, and corrosive environments, and can play a certain isolation role and delay the attenuation of the magnet performance.
[0041] In the specific implementation of the present invention, the thickness of the lubricating layer 102 can be adjusted according to actual conditions. Specifically, the thickness of the lubricating layer 102 is 10-30 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm or any two thereof.
[0042] The lubricating layer 102 may be composed of a lubricant material. In some embodiments, the lubricating layer 102 contains a lubricant. Preferably, the lubricant includes at least one of polytetrafluoroethylene, boron nitride, stearate, and molybdenum disulfide. The stearate may include at least one of zinc stearate, calcium stearate, and lithium stearate. These lubricant materials can not only provide excellent lubrication performance, but also remain stable under high temperature and high pressure environments, and are suitable for magnet applications under various extreme working conditions.
[0043] Magnetic materials are the basis of magnets and play a decisive role in the magnetic properties of magnets. In some embodiments, the magnetic material includes at least one of NdFeB magnetic powder, SmFeN magnetic powder, and SmCo magnetic powder. Among them, NdFeB magnetic powder is an alloy magnetic powder composed of neodymium (Nd), iron (Fe), and boron (B), and has a high magnetic energy product and coercive force; SmFeN magnetic powder is an alloy magnetic powder composed of samarium (Sm), iron (Fe) and nitrogen (N), and has a high temperature stability; SmCo magnetic powder is an alloy magnetic powder composed of samarium (Sm) and cobalt (Co), and has excellent temperature stability and corrosion resistance. In the actual production process, the corresponding magnetic material can be selected according to actual needs.
[0044] The bonding material can effectively bond the magnetic material particles together to form a strong magnet structure. After curing, the bonding material can provide sufficient bonding strength to ensure that the magnet will not easily break or delaminate when subjected to mechanical stress. In some embodiments, the bonding material includes an epoxy resin binder, such as bisphenol A epoxy resin, which can not only fully meet the requirements for the preparation of anisotropic bonded magnets, but also has excellent insulation properties, so that it can prevent the loss of magnetic field inside the magnet, thereby maintaining the magnetic properties of the magnet; the epoxy resin binder also has excellent chemical stability and is not susceptible to chemical corrosion, which enables the magnet to maintain its structural integrity and magnetic properties under various harsh conditions. Among them, the epoxy resin binder can be a thermosetting epoxy resin.
[0045] In some embodiments, the mass ratio of magnetic material to bonding material is 100:(1.5-3.5). By controlling the amount of bonding material added, the abundance of magnetic material in the magnet is ensured, which helps the magnet maintain a high magnetic energy product and coercive force, thereby maintaining its excellent magnetic properties; the bonding material plays a role in connecting magnetic material particles in the magnet, providing mechanical strength and stability of the magnet. By limiting the mass ratio of magnetic material to bonding material to 100:(1.5-3.5), it can be ensured that the magnet is not easy to break during molding and use, and has sufficient mechanical strength.
[0046] Specifically, the mass ratio of the magnetic material to the bonding material is 100:(1.5-3.5), for example, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5 or a range consisting of any two thereof.
[0047] In some embodiments, the mass ratio of the magnetic material to the lubricant in the lubricating layer 102 is 100:(0.1-1.0), such as 100:0.1, 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1.0 or any two of them. By limiting the mass ratio of the magnetic material to the lubricant, it can be ensured that the magnet has good mechanical properties and environmental resistance while maintaining high magnetic properties, while reducing production costs and improving production efficiency and yield rate.
[0048] The anisotropic bonded magnet of the present invention has excellent magnetic properties and mechanical properties. In some embodiments, the radial crushing strength (also called radial compressive strength) of the anisotropic bonded magnet can reach more than 100 MPa, specifically 100 to 120 MPa. The radial crushing strength is used to evaluate the destructive strength of a magnet when it is subjected to radial pressure. It is an important indicator for measuring the mechanical properties of a magnet. The test standard of GBT-6804-2008 can be referred to. The specific test method is as follows: a preload pressure less than the destructive strength is applied to the magnet sample to be tested (which can be cylindrical) to ensure that there is no gap between the sample and the fixture and the surface of the magnet is flat; then the radial pressure is gradually increased until the magnet sample to be tested is destroyed. The loading speed can be 1 mm / min; at the moment of the magnet sample being destroyed, the destructive pressure value displayed by the testing machine is recorded, and multiple magnet samples of the same size to be tested are tested, and the destructive pressure of each sample is recorded, and the average value is calculated to obtain the radial crushing strength of the magnet.
[0049] A second aspect of the present invention provides a method for preparing the anisotropic bonded magnet according to the first aspect, comprising the following steps:
[0050] S1, mixing magnetic material and bonding material to obtain mixed rubber magnetic powder;
[0051] S2, performing a first pressing on the mixed rubber magnetic powder to obtain a first compact;
[0052] S3, spraying a lubricant solution on the outer surface of the first green compact, and obtaining an intermediate after drying;
[0053] S4, placing the intermediate in a magnetic field for a second pressing to obtain a second green compact;
[0054] S5, solidifying the second green compact to obtain anisotropic bonded magnet.
[0055] Specifically, in step S1, the magnetic material and the bonding material are mixed in an organic solvent. The function of the organic solvent is to dissolve the bonding material so that it can be evenly wrapped on the surface of the magnetic material to form a stable mixed glue state to obtain a mixture. Subsequently, the organic solvent in the mixture is removed by a vacuum process, so that the bonding material forms a thin solid film layer on the surface of the magnetic material, thereby obtaining a mixed glue magnetic powder. This process ensures the bonding between the magnetic material and the bonding material, while maintaining the dispersibility of the magnetic material, providing preparation for the subsequent pressing step.
[0056] In step S2, the mixed rubber magnetic powder obtained in S1 is subjected to a first pressing under appropriate conditions to form a first green compact. The first pressing process can be performed by means of die vibration or core rod vibration to uniformly fill the mixed rubber magnetic powder into the die cavity to avoid forming voids. The first green compact having a shape and size is formed by the first pressing.
[0057] In step S3, a lubricant solution is sprayed on the outer surface of the first green compact to form a coating layer formed of the lubricant solution; then the solvent in the coating layer is volatilized by a second drying process, and the remaining lubricant is solidified on the surface of the first green compact to form a lubricating layer 102, thereby obtaining an intermediate. Spraying refers to spraying the lubricant solution in a mist form onto the outer surface of the first green compact.
[0058] In step S4, the intermediate is subjected to a second pressing and oriented under the action of a magnetic field. The second pressing under the action of a magnetic field ensures that the magnetic material particles can be orderly arranged along the direction of the magnetic field to form an anisotropic structure, thereby obtaining a second compact.
[0059] In step S5, the second compact needs to be solidified under certain temperature and time conditions to further enhance the stability of the internal structure of the magnet. The solidification process can help the bonding material to completely harden and form a solid network structure to firmly bind the magnetic material particles together.
[0060] The present invention sprays the lubricant on the outer surface of the first green compact instead of mixing it into the interior of the magnet, which can not only effectively realize demoulding, but also effectively avoid the influence of the lubricant on the internal structure and performance of the magnet, thereby improving the magnetic properties and mechanical properties. Compared with the traditional powder mixing method, the present invention sprays the lubricant on the surface, which is simpler and easier to operate, and can process multiple batches of green compacts at one time, thereby improving production efficiency, reducing production costs, and also reducing impurities or operating errors introduced due to complex processes.
[0061] The present invention does not limit the specific selection of raw materials, which can be conventional compounds in the art. For example, the lubricant solution can be a solution formed by a lubricant and an organic solvent. In some embodiments, the lubricant includes at least one of polytetrafluoroethylene, boron nitride, stearate, and molybdenum disulfide, and the stearate includes at least one of zinc stearate, calcium stearate, and lithium stearate; and / or, the magnetic material includes at least one of NdFeB magnetic powder, SmFeN magnetic powder, and SmCo magnetic powder; and / or, the bonding material includes an epoxy resin bonding agent; and / or, the organic solvent is n-hexane.
[0062] The present invention does not limit the mass ratio of each raw material, which can be adjusted according to actual needs. For example, in some embodiments, the mass ratio of the magnetic material to the bonding material is 100:(1.5-3.5), such as 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5 or a range consisting of any two of them; and / or, the mass ratio of the magnetic material to the lubricant is 100:(0.1-1.0), such as 100:0.1, 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1.0 or a range consisting of any two of them.
[0063] In some embodiments, the density of the first compact is 3-5 g / cm 3 , for example 3g / cm 3 、3.5g / cm 3 、3.8g / cm 3 , 4g / cm 3 , 4.2g / cm 3 4.5g / cm 3 , 5g / cm 3 Or a range consisting of any two of them.
[0064] In some embodiments, the drying temperature is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C or a range consisting of any two thereof, and the drying time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h or a range consisting of any two thereof.
[0065] The spraying parameters are key factors affecting the spraying quality and effect. The spraying is air spraying. In some embodiments, the nozzle used for spraying has a diameter of 1 to 3 mm, a gas pressure of 0.2 to 0.6 MPa, a spraying height of 10 to 30 cm, a spray gun angle of 45°, a flow rate of 0.5 to 10.0 L / min, and a spraying speed of 10 to 50 cm / s.
[0066] In some embodiments, the strength of the magnetic field is 1.5-2 T, for example, 1.5 T, 1.6 T, 1.7 T, 1.8 T, 1.9 T, 2 T or a range consisting of any two thereof.
[0067] In some embodiments, the second pressing temperature is 100-200°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or a range consisting of any two thereof.
[0068] The present invention can accurately control the curing of the bonding material by adjusting the temperature and time, and can adjust the curing parameters according to actual needs to optimize the mechanical properties and magnetic properties of the magnet. In some embodiments, the curing temperature is 150-200°C, such as 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or any two thereof, and the curing time is 60-90 minutes, such as 60 minutes, 65 minutes, 70 minutes, 75 minutes, 80 minutes, 85 minutes, 90 minutes or any two thereof.
[0069] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0070] Example 1
[0071] The preparation method of the anisotropic bonded magnet in this embodiment comprises the following steps:
[0072] S1, 80 g Nd2Fe 14 B magnetic powder, 10g Sm2Fe 17 N, 10 grams of SmCo5 magnetic powder, 2 grams of E20 epoxy resin binder and solvent are uniformly mixed, and the solvent is removed in vacuum at 50°C to obtain mixed powder; the mass of the epoxy resin binder is 2% of the mass of the magnetic powder;
[0073] S2, placing the mixed rubber powder in the mold cavity, using the concave mold vibration or core rod vibration method to ensure the uniformity of the mixed rubber powder, after the first pressing, the density is 3.8g / cm 3 a first compact of
[0074] S3, spraying the lubricant solution on the entire outer surface of the first green compact, with a nozzle diameter of 1.0 mm, an air pressure of 0.4 MPa, a spraying height of 15 cm, a spray gun angle of 45°, a flow rate of 6.0 L / min, and a spraying speed of 50 cm / s; then drying at 50°C for 2 hours to form a lubricating layer with a thickness of 10 μm covering all surfaces of the first green compact, the mass of polytetrafluoroethylene being 0.3% of the mass of the magnetic powder, to obtain an intermediate; wherein the lubricant solution is a n-hexane solution containing polytetrafluoroethylene, and the mass ratio of n-hexane to polytetrafluoroethylene is 95:5;
[0075] S4, placing the intermediate into a molding press, and performing orientation molding at a temperature of 150° C. and a magnetic field of 1.5 T to obtain a second green compact;
[0076] S5, curing the second green compact at 200°C for 60 minutes to obtain anisotropic bonded magnet.
[0077] Example 2
[0078] The difference from Example 1 is that in S3, a lubricating layer with a thickness of 20 μm is formed, and the mass of polytetrafluoroethylene is 0.6% of the mass of the magnetic powder.
[0079] Example 3
[0080] The difference from Example 1 is that in S3, a lubricating layer with a thickness of 30 μm is formed, and the mass of polytetrafluoroethylene is 0.9% of the mass of the magnetic powder.
[0081] Example 4
[0082] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing boron nitride, forming a lubricating layer with a thickness of 10 μm, and the mass of the boron nitride is 0.3% of the mass of the magnetic powder.
[0083] Example 5
[0084] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing boron nitride, forming a lubricating layer with a thickness of 20 μm. The mass of the boron nitride is 0.6% of the mass of the magnetic powder.
[0085] Example 6
[0086] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing boron nitride, forming a lubricating layer with a thickness of 30 μm. The mass of the boron nitride is 0.9% of the mass of the magnetic powder.
[0087] Example 7
[0088] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing zinc stearate, forming a lubricating layer with a thickness of 10 μm, and the mass of the zinc stearate is 0.3% of the mass of the magnetic powder.
[0089] Example 8
[0090] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing zinc stearate, forming a lubricating layer with a thickness of 20 μm, and the mass of the zinc stearate is 0.6% of the mass of the magnetic powder.
[0091] Example 9
[0092] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing zinc stearate, forming a lubricating layer with a thickness of 30 μm, and the mass of zinc stearate is 0.9% of the mass of the magnetic powder.
[0093] Example 10
[0094] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing molybdenum disulfide, forming a lubricating layer with a thickness of 10 μm, and the mass of molybdenum disulfide is 0.3% of the mass of the magnetic powder.
[0095] Embodiment 11
[0096] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing molybdenum disulfide, forming a lubricating layer with a thickness of 20 μm, and the mass of molybdenum disulfide is 0.6% of the mass of the magnetic powder.
[0097] Example 12
[0098] The difference from Example 1 is that in S3, the lubricant solution is a n-hexane solution containing molybdenum disulfide, and the mass of molybdenum disulfide is 0.9% of the mass of the magnetic powder.
[0099] Comparative Example 1
[0100] The preparation method of the anisotropic bonded magnet of this comparative example comprises the following steps:
[0101] S1, 80 g Nd2Fe 14 B magnetic powder, 10g Sm2Fe 17 N, 10 grams of SmCo5 magnetic powder, 2 grams of E20 epoxy resin binder and solvent are uniformly mixed, and the solvent is removed by vacuum at 50°C to obtain mixed powder; the mass of the epoxy resin binder is 2.0% of the mass of the magnetic powder;
[0102] S2, mixing 100 g of the mixed rubber powder with 0.3 g of polytetrafluoroethylene powder to obtain composite magnetic powder;
[0103] S3, placing the composite magnetic powder in the mold cavity, using the concave mold vibration or core rod vibration method to ensure uniform filling, after the first pressing, the density is 3.8g / cm 3 a first compact of
[0104] S4, placing the first green compact into a molding press, and performing orientation molding at a temperature of 150° C. and a magnetic field of 1.5 T to obtain a second green compact
[0105] S5, curing the second green compact at 200°C for 60 minutes to obtain anisotropic bonded magnet.
[0106] Comparative Example 2
[0107] The difference from Comparative Example 1 is that in S2, polytetrafluoroethylene is replaced by boron nitride.
[0108] Comparative Example 3
[0109] The difference from Comparative Example 1 is that in S2, polytetrafluoroethylene is replaced by zinc stearate.
[0110] Comparative Example 4
[0111] The difference from Comparative Example 1 is that in S2, polytetrafluoroethylene is replaced by molybdenum disulfide.
[0112] Test example
[0113] 1. Magnetic performance test
[0114] Refer to GB / T 43264-2023 Permanent magnet surface magnetic field distribution test method
[0115] 2. Magnet radial crushing strength test
[0116] Refer to GB / T 43264-2023 Test method for magnetic field distribution on the surface of permanent magnets.
[0117] The test results are shown in Table 1.
[0118] Table 1
[0119]
[0120]
[0121] According to Table 1, compared with the powder mixing method of the comparative example, Examples 1-12 form a lubricating layer on the outer surface of the magnetic body by spraying, which can significantly improve the mechanical properties of the magnet, and can achieve an average surface magnetism ≥ 2500Gs and a radial crushing strength of the magnet ≥ 100MPa.
[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An anisotropic bonded magnet, characterized in that: The anisotropic bonded magnet comprises a magnetic body (101) and a lubricating layer (102); the lubricating layer (102) is located on the outer surface of the magnetic body (101), and the magnetic body (101) comprises a magnetic material and a bonding material.
2. The anisotropic bonded magnet according to claim 1, characterized in that: The thickness of the magnetic body (101) is 1 to 4 mm; And / or, the lubricating layer (102) has a thickness of 10 to 30 μm.
3. The anisotropic bonded magnet according to claim 1 or 2, characterized in that: The lubricating layer (102) contains a lubricant; preferably, the lubricant includes at least one of polytetrafluoroethylene, boron nitride, molybdenum disulfide, and stearate.
4. The anisotropic bonded magnet according to any one of claims 1 to 3, characterized in that: The magnetic material includes at least one of NdFeB magnetic powder, SmFeN magnetic powder and SmCo magnetic powder; and / or, The bonding material includes an epoxy resin adhesive.
5. The anisotropic bonded magnet according to any one of claims 2 to 4, characterized in that: The mass ratio of the magnetic material to the bonding material is 100:(1.5-3.5); and / or, The mass ratio of the magnetic material to the lubricant in the lubricating layer (102) is 100:(0.1-1.0).
6. A method for preparing the anisotropic bonded magnet according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing magnetic material and bonding material to obtain mixed rubber magnetic powder; S2, performing a first pressing on the mixed rubber magnetic powder to obtain a first compact; S3, spraying a lubricant solution on the outer surface of the first green compact, and obtaining an intermediate after drying; S4, placing the intermediate in a magnetic field for second pressing to obtain a second compact; S5, solidifying the second green compact to obtain anisotropic bonded magnet.
7. The preparation method according to claim 6, characterized in that: The lubricant solution is formed by mixing a lubricant and an organic solvent, wherein the lubricant includes at least one of polytetrafluoroethylene, boron nitride, molybdenum disulfide, and stearate, and the organic solvent is n-hexane; and / or, The magnetic material includes at least one of NdFeB magnetic powder, SmFeN magnetic powder and SmCo magnetic powder; and / or the bonding material includes epoxy resin bonding agent; The mass ratio of the magnetic material to the bonding material is 100:(1.5-3.5); and / or, The mass ratio of the magnetic material to the lubricant is 100:(0.1-1.0); and / or, The density of the first compact is 3-5 g / cm 3 .
8. The preparation method according to claim 6, characterized in that: The spraying is air spraying, the nozzle used for the spraying has a diameter of 1-3 mm, the gas pressure is 0.2-0.6 MPa, the spraying height is 10-30 cm, the spray gun angle is 45°, the flow rate is 0.5-10.0 L / min, and the spraying speed is 10-50 cm / s; The drying temperature is 40-60° C., and the drying time is 1-3 hours.
9. The preparation method according to claim 6, characterized in that: The temperature of the first pressing is 10-30° C.; and / or the temperature of the second pressing is 100-200° C., and the intensity of the magnetic field is 1.5-2T.
10. The preparation method according to claim 6, characterized in that: The curing temperature is 150-200° C., and the curing time is 60-90 minutes.